1980
DOI: 10.1007/bf01055546
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings in workers exposed to pentachlorophenol

Abstract: Comparative findings are presented on the health and exposure status of groups of individuals in Hawaii with and without occupational exposure to pentachlorophenol (PCP). Occupational exposure to PCP occurred through employment at firms engaged in the treatment of wood with either PCP alone or PCP plus other compounds as preservative chemicals. Mean serum levels were 0.32 ppm for 32 control individuals, 1.72 ppm for 24 workers exposed to PCP and other wood preservative chemicals, and 3.78 ppm for 22 workers ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In another study enrolling 46 subjects with occupational exposure to PCP, an increased prevalence of low-grade infections and inflammations of the skin, subcutaneous tissues, eyes and upper respiratory tract mucosa has been reported. Strong to moderate statistical associations were observed between PCP exposure and increased immature leucocytes and basophils, raised plasma cholinesterase, alkaline phosphatase, IgG and uric acid, with decreased serum calcium [56]. Several studies have reported an association between diminished lymphocyte proliferative response to mitogens and exposure to PCP [46,55,57,58].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 94%
“…In another study enrolling 46 subjects with occupational exposure to PCP, an increased prevalence of low-grade infections and inflammations of the skin, subcutaneous tissues, eyes and upper respiratory tract mucosa has been reported. Strong to moderate statistical associations were observed between PCP exposure and increased immature leucocytes and basophils, raised plasma cholinesterase, alkaline phosphatase, IgG and uric acid, with decreased serum calcium [56]. Several studies have reported an association between diminished lymphocyte proliferative response to mitogens and exposure to PCP [46,55,57,58].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 94%
“…Incidents of low grade respiratory infections and the development of inflammation of the skin of PCP exposed workers have been reported [14]. Increased levels of Creactive protein, which is often elevated in various inflammatory disorders has also been documented [15].…”
Section: Discussionmentioning
confidence: 99%
“…PCP was used as an insecticide and fungicide [compare Klemmer et al, 1980]. Extensive published reports have described the toxic effects, resulting in a ban of PCP production and trade in 1989 in Germany.…”
Section: Introductionmentioning
confidence: 99%